Reduction in SGLT1 mRNA Expression in the Ventromedial Hypothalamus Improves the Counterregulatory Responses to Hypoglycemia in Recurrently Hypoglycemic and Diabetic Rats - Fan, Xiaoning (Diabetes, 2015)
The objective of this study was to determine whether the sodium-glucose transporter SGLT1 in the ventromedial hypothalamus (VMH) plays a role in glucose sensing and in regulating the counterregulatory response to hypoglycemia, and if so, whether knockdown of in the VMH can improve counterregulatory responses to hypoglycemia in diabetic rats or rats exposed to recurrent bouts of hypoglycemia (RH). Normal Sprague-Dawley rats as well as RH or streptozotocin (STZ)-diabetic rats received bilateral VMH microinjections of an adenoassociated viral vector containing either the SGLT1 short hairpin RNA (shRNA) or a scrambled RNA sequence. Subsequently, these rats underwent a hypoglycemic clamp to assess hormone responses. In a subgroup of rats, glucose kinetics was determined using tritiated glucose. The shRNA reduced VMH SGLT1 expression by 53% in nondiabetic rats, and this augmented glucagon and epinephrine responses and hepatic glucose production during hypoglycemia. Similarly, SGLT1 knockdown improved the glucagon and epinephrine responses in RH rats and restored the impaired epinephrine response to hypoglycemia in STZ-diabetic animals. These findings suggest that SGLT1 in the VMH plays a significant role in the detection and activation of counterregulatory responses to hypoglycemia. Inhibition of SGLT1 may offer a potential therapeutic target to diminish the risk of hypoglycemia in diabetes.